Instruments of a strategic foreign economic policy: Study for the German Federal Foreign Office - Katrin Kamin; Kerstin Bernoth; Gabriel Felbermayr; Marcel Fratzscher; Mia Hoffmann; Niclas Poitiers; Malte Rieth; Pauline Weil; Guntram B. Wolff; Georg Zachmann; Jacqueline Dombrowski; Sebastian Horn; et al. (Institute for the World Economy (IfW), 2021)
The separation of security and economic objectives in foreign policy, which was often sought in international political issues in the past, has outlived its usefulness. The transition to a more power-based order can be felt around the world. International economic instruments and agreements are increasingly used to achieve various foreign policy goals. These are simultaneously used to promote own political interests, sometimes to the detriment of partner countries. This "weaponized interdependence" makes it necessary for Germany and the European Union to assess their vulnerabilities and to design their own defensive and offensive strategies. The Kiel Institute for the World Economy, together with DIW Berlin and Bruegel, has produced a study on behalf of the Federal Foreign Office that addresses the objectives, instruments, and trade-offs of a strategic foreign economic policy and describes how to deal with them in the context of German and European policy making.
Additional information: Study by IfW Kiel, Bruegel and DIW Berlin
Keywords: F4; F5; L5; Q58; 330; Foreign economic policy; Geopolitics; Industrial policy; International competition; Current account; International financial system; Balance of payments; Virtual currency; Außenwirtschaftspolitik; Geopolitik; Industriepolitik; Internationaler Wettbewerb; Leistungsbilanz; Internationales Finanzsystem; Zahlungsbilanz; Virtuelle Währung; Welt